Intranasal squamous cell carcinoma in a renal transplant recipient on long term immunosuppression. Issue 745 (November 1987) - Pace-Balzan, A.; Timms, M. S.
Abstract : An increased risk of developing malignant disease after renal transplantation and immunosuppression with azathioprine and corticosteroids is well documented. We report a case of intranasal carcinoma occurring in a renal transplant recipient. The possible role of immunosuppression on the development and on the outcome of treatment of this tumour is discussed.